Pengaruh Profil Risiko, Tata Kelola dan Permodalan Terhadap Profitabilitas (Studi Bank Umum Konvensional periode 2012-2015) - Rofika Wulandari; Imam Mas’ud; Ahmad Roziq (UPT Penerbitan Universitas Jember, 2018)
Profitabilitiy as on of indicators wich can be used as baseline to look on financial performance of the company. Profitability also used as one of methods on measuring health performance of the banking industry. This research purpose to test the influence risk profile, good corporate governance (GCG) and capital (CAR) to the profitability of banks which measured by ROA. The sample on this research used purposive sampling method, researcher used 30 conventional banks wich listed on Indonesia Stock Exchange on 2012 – 2015. Analysis technicue in this research used multiple linear regression. The result of F test shown that independent variables impact the dependent variable significantly. The of result t test shown that risk profile has negative impact to Profitability, GCG and CAR has positive impact to Profitability. The result of adjusted R2 shown 26,5% means that dependent variable can explain by indpendent variables only 26,5% and 73,5% explain by others factors which didn’t use as variable in this research. Keywords: risk profile, GCG, CAR, Profitability